Strength Analysis of High Density Polyethylene Floating Jetty Deck with Finite Element Method - Kharis Abdullah; Aditya Maharani; Sryang T Sarena (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Floating Jetty or commonly called a floating dock, is one of the facilities in the harbour for loading and unloading passengers from ships to land or vice versa. HDPE (High-density polyethene) is a type of plastic that is more resistant to chemical solutions or contaminants and can be recycled. HDPE (High Density Polyethylene) material can be used for marine building construction. At the design stage, there is a stage to determine the strength of marine building construction to avoid failure in its operation. One of the methods used to analyse structural strength is the finite element method. In this study, the strength of floating dock decks made from HDPE is analysed using the finite element method. The results of modelling using finite elements show that the construction of floating dock decks made from HDPE has a von mises stress of 3.05 Mpa and a deformation of 0.0035 mm which is still below the allowable stress and deformation values determined by the classification society.